ML-Optimized Beam-based Radio Coverage Processing in IEEE 802.11 WLAN Networks - Mehdi Guessous; Lahbib Zenkouar (IAES Indonesia Section, 2018)
Dynamic Radio Resource Management (RRM) is a major building block of Wireless LAN Controllers (WLC) function in WLAN networks. In a dense and frequently changing WLANs, it maximizes Wireless Devices (WD) opportunity to transmit and guarantees conformance to the design Service Level Agreement (SLA). To achieve this performance, a WLC processes and applies a network-wide optimized radio plan based on data from access points (AP) and upper-layer application services. This coverage processing requires a